1957
DOI: 10.4141/cjss57-002
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Elevation of a Mountain Stream to Reaction and Salt Content of Water and Soil

Abstract: Water samples were obtained from a number of mountain lakes and irrigation reservoirs in the Okanagan Valley, and from streams emptying them. It was found that in any one drainage basin, the water had a higher pH and salt content at low elevation than at high elevation.A more detailed investigation was conducted in the Mission Creek watershed. With decreasing elevation the following relationships were found: (a) increasing pH, electrical conductivity, and contents of calcium, potassium and sodium in the stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…This result conforms to the findings of Lottıg et al (2011), who noted the significant chemical differences between streams and lakes because of the inputs (flow regimes) to them. In addition, the negative relationships of these variables with elevation were also reported by Wılcox et al (1957) and Yavuzatmaca (2020b). Electrical conductivity and elevation were also showed to cause the heterogeneities among three water basins in Turkey (Yavuzatmaca 2019).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This result conforms to the findings of Lottıg et al (2011), who noted the significant chemical differences between streams and lakes because of the inputs (flow regimes) to them. In addition, the negative relationships of these variables with elevation were also reported by Wılcox et al (1957) and Yavuzatmaca (2020b). Electrical conductivity and elevation were also showed to cause the heterogeneities among three water basins in Turkey (Yavuzatmaca 2019).…”
Section: Discussionsupporting
confidence: 65%
“…These streams start from high altitude and flow towards lower altitude by collecting water that allows one to think that their hydro morphological structures and environmental conditions are very similar to each other when compared to lakes. The reason is that snow and rainwater with low percolates into the soil directly flow to the stream bed at high elevations since the soil here is saturated with water and there is less transpiration (Wılcox et al 1957). They also reported an increasing trend in the pH and salt contents of the soil profiles of the Mission Creek watershed from 6180 (1883.7 m asl.)…”
Section: Discussionmentioning
confidence: 99%
“…It was explained by lower decomposition rate of organic matter compared to the higher elevation. Therefore, it seems that TOC accumulates in the soil of higher elevations (18,19). In a similar research, it was reported that increasing altitude has a positive significant effect on organic matter in soil.…”
Section: Effect Of Elevation On Tocmentioning
confidence: 72%
“…The other environmental factors retained by the forward selection procedure are closely related to altitude. For instance a negative correlation between conductivity and elevation is generally observed (Wilcox et al, 1957;Rundle et al, 1993) and the positive correlation between altitude and the percentage of boulders reflects the sediment transport implying the presence of larger rocks mainly in the upstream part and finer sediments in the downstream part. This altitudinal distribution of habitats is underlined by a clear differentiation of the taxa distribution.…”
Section: Discussion -Conclusionmentioning
confidence: 99%